Sodium-glucose cotransporter 2 inhibition: towards an indication to treat diabetic kidney disease. (31st January 2020) - Górriz, Jose Luis; Navarro-González, Juan F; Ortiz, Alberto; Vergara, Ander; Nuñez, Julio; Jacobs-Cachá, Conxita; Martínez-Castelao, Alberto; Soler, Maria Jose
Abstract: Sodium-glucose cotransporter 2 inhibitors (SGLT2i) have clearly demonstrated their beneficial effect in diabetic kidney disease (DKD) on top of the standard of care [blood glucose control, renin–angiotensin system blockade, smoking cessation and blood pressure (BP) control], even in patients with overt DKD. However, the indication of this drug class is still blood glucose lowering in type 2 diabetic patients with estimated glomerular filtration rate >45 mL/min/1.73 m 2 . Based on the new evidence, several scientific societies have emphasized the preferential prescription of SGLT2i for patients at risk of heart failure or kidney disease, but still within the limits set by health authorities. A rapid positioning of both the European Medicines Agency and the US Food and Drug Administration will allow patients with overt DKD to benefit from SGLT2i. Clinical experience suggests that SGLT2i safety management may in part mirror renin–angiotensin blockade safety management in patients with overt DKD. This review focuses on the rationale for an indication of SGTL2i in DKD. We further propose clinical steps for maximizing the safety of SGLT2i in DKD patients on other antidiabetic, BP or diuretic medication.